Intolerable cruelty [videorecording (Blu-Ray)] - Coen, Joel; Coen, Ethan; Clooney, George; Zeta-Jones, Catherine, 1969-; Thornton, Billy Bob; Ramsey, Robert, 1962-; Stone, Matthew, 1963-; Burwell, Carter (Universal Studios Home Entertainment, 2014)
After a Beverly Hills lawyer gets his client out of his marriage without having to pay a settlement by setting up the wife, she sets out to seek revenge. She is planning to get the lawyer to fall in love with her so she can take him for all he's got!